Planejamento estratégico de uma oficina de bombas injetoras na região de Constantina-RS - Pruciano, Susan Machado Soares (2023)
The present study has as its main objective to identify strategies generated by strategic planning, for a diesel mechanic services company, without causing impacts in competitiveness. Thus, the methodology applied consisted in a mixed research formulation (qualitative and quantitative), in exploratory and descriptive character, contemplating a case study in a fuel injector pump repair shop in the region of Constantina/RS, done through research next to the manager and customers of the company. With the study realization, it was concluded that the company has most great points in its internal environment and threats in its external environment, characterizing the predominance of a strategic maintenance posture. Besides that, an action plan realization to the company contributed to the detailing of the strategies needed by the company, especially in the quality of the offered services, the prices and the sales, among other factors.